Ordinary AV Nodal Reentry Tachycardia-Unusual Ablation: A Case Report and Review of the Literature - Franz Haertel; P. Christian Schulze; Anett Große; Dirk Prochnau; Ralf Surber (Case Reports in Cardiology)
A 72-year-old woman was referred to us with typical symptoms of paroxysmal supraventricular tachycardia for electrophysiological diagnostics and catheter ablation. During the first session of catheter ablation, a probing of the right ventricle was not successful. Therefore, an angiography of the central veins was performed. A rare anatomical variation with atresia of the inferior vena cava below the hepatic veins with azygos persistence was detected. The blood of the lower half of the body was drained via the dilated azygos into the superior vena cava; the blood of the liver veins enters into the right atrium directly. By atypical catheter placement over the azygos vein in the right ventricle and coronary sinus, an AV nodal reentry tachycardia (AVNRT) could be confirmed as the mechanism of tachycardia. However, a stable position of the ablation catheter could not be achieved by the femoral approach, so the successful AV node modulation with ablation of the slow pathway was performed via jugular access.